Generalisasi Pakaian Muslim Menjadi Modest Wear pada Tren Fashion Indonesia Tahun 2010-an: - - Ratuannisa, Tyar (Practice of Fashion and Textile Education Journal, 2024)
Indonesia is a country with the largest Muslim population in the world and with a diversity of languages, culture, and religious beliefs. From time to time, fashion trends in Indonesia are associated with the process of how an appropriate idea can be accepted and internalized through the filtration of Indonesian culture. Modest wear derived from Muslim wear does not only serve as a physiological fulfilment but also a need for identity. There are two types of modest wear users. The first ones are those who use it as an identity, they do not care about trends and will continue to use them. Meanwhile, the second ones are those who choose modest wear to keep up with the trend. This phenomenon raises an idea that, for a Muslim woman, the basis of clothing using modest wear is to use the hijab/jilbab/kerudung as part of the basic clothing. However, many also use head coverings temporarily and do not last long. Thus, this commitment to modest choices becomes a mere trend at one time or, in other words, the use of hijab does not represent their identity. This study investigates the change in Indonesia regarding hijab identity diachronically and the reinterpretation of modest wear in the 2010s accompanied by the determinant factors viewed from the synchronic aspects. It was revealed that modest wear was acceptable due to the dominant factors of trend drivers that are interconnected and interdependent, namely world events, economic conditions, social change, entertainment world, technological innovation, and fashion leaders in Indonesia.